Reverse mentoring : how young leaders can transform the church and why we should let them - Creps, Earl G.; Leadership Network (Dallas, Tex.) (San Francisco, CA : Jossey-Bass, 2008)
"Earl Creps is known for his work in connecting the younger generation of postmoderns with their Boomer predecessors. The author of Off-Road Disciplines, Creps, in this new book, takes up the topic of how older church leaders can learn from younger leaders who are more conversant with culture, technology, and social context. In addition to making the benefits of what he calls "reverse mentoring" apparent, he also makes it accessible by offering practical steps to implement this discipline at both personal and organizational levels, particularly in communication, evangelism, and leadership." "Creps' new book is a topic of interest both inside and outside the church as older leaders realize that they're not "getting it" when it comes to technologies (iPod, IM, blogging) or cultural issues such as the fact that younger people see the world in an entirely different way. Creps has been personally involved in reverse mentoring for several years and has spoken and written on the subject extensively. He has pastored three churches (one Boomer, one Builder, on X'er) and is currently a church planter in Berkeley, California. He has also served as a consultant and and a seminary professor and administrator, holding a PhD in Communication Studies and a D. Min. from the Assemblies of God Theological Seminary."--Jacket.
Introduction: It takes a child to raise a village -- PART 1: Facing reality. Identity: "I am not cool" -- Culture: "I don't get it" -- Ministry: "I am not relevant" -- -- PART 2: Cultivating spirituality. Vision: seeing beyond ourselves -- Wisdom: knowing beyond our information -- Relationship: befriending beyond our peers -- -- PART 3: Experiencing practicality. Evangelism: learning from outsiders -- Communication: learning from listeners -- Leadership: learning from followers -- -- PART 4: Developing reciprocity. Proteges: developing R-mentoring relationships -- Processes: embedding R-mentoring in organizations -- Interview: Joel and Rachel Mentor Earl and Janet -- I was so much older then; I'm younger than that now.
"A Leadership Network publication."
Includes bibliographical references (p. 185-198) and index.
Keywords: Christian leadership; Christian youth -- Religious life; Church renewal